Alteration of subjective feelings in football players undertaking their usual training and match schedule during the Ramadan fast - Leiper, J. B.; Junge, A.; Maughan, R. J.; Zerguini, Y.; Dvorak, J. (Journal of Sports Sciences, 2008)
Eighty-seven players (54 fasting players, 33 non-fasting players) who carried out their club's scheduled training and competitive matches completed the daily questionnaire before and during Ramadan. Fasting players trained on average 11 h after their last food and drink. While fasting players reported that they were slightly less ready to train during the Ramadan fast than in the period before Ramadan, there was no increase in their perceived effort during training or in training difficulty compared with their ratings before Ramadan, or with those of the non-fasting group during Ramadan. The fasting players were marginally more thirsty, hungry and tired, and slightly less able to concentrate before training during Ramadan than in the pre-Ramadan period. Before Ramadan, both groups averaged more than 9 h sleep each night. The non-fasting players recorded that they had about 105 min less sleep per night during the first week of Ramadan, before reverting back to their pre-Ramadan amount of sleep. The fasting group consistently reported having about 1 h less sleep per night throughout Ramadan, but neither group appeared to find sleep quality to have altered. In the first 2 weeks after Ramadan, the modest changes reported by the fasting players reverted back to their pre-Ramadan values.